Comparative toxicity effect of organic and inorganic substances in palm oil mill effluent (POME) using native microalgae species. (April 2020) - Jasni, Jannatulhawa; Arisht, Shalini Narayanan; Mohd Yasin, Nazlina Haiza; Abdul, Peer Mohamed; Lin, Sheng-Kai; Liu, Chun-Min; Wu, Shu-Yii; Jahim, Jamaliah Md; Takriff, Mohd Sobri
Highlights: The response of mix-culture microalgae was observed on organic and inorganic substances. Acetic, butyric, formic and propionic acids promote microalgae growth at both short and long-term exposure. Copper, as well as oil and grease, suppress microalgae growth during short-term exposure. The most favorable growth rates of microalgal were in the range of pH 7-9. POME can be used as renewable media for microalgae growth. Abstract: Phycoremediation of palm oil mill effluent (POME) using native microalgae promotes sustainable agricultural wastewater treatment technology. However, POME is characterized by a high amount of organic and inorganic compounds. Therefore, the aim of this paper is to study the toxic effect of selected organic (acetic acid, butyric acid, propionic acid, formic acid, oil and grease) and inorganic (copper) compounds presence in POME on the microalgae population. A mix-culture of three native microalgae species consisted of Coelastrella sp. UKM 4, Chlorella sp. UKM 8 and Scenedesmus sp. UKM 9 were exposed for 120 h to different organic and inorganic substances. Then, microalgae growth response, the changes of pH and the half-maximal effective concentration (EC50 ) were studied for both short-term (24 h) and long-term (96 h) exposure. The EC50 indicated that acetic, butyric, formic and propionic acids promote microalgae growth at both short and long-term exposure (survival rate >50 % at all selected concentrations) whereas copper, as well as oil and grease, suppress microalgae growth (survival rate <50 %) during short-term exposure. The most favorable growth rates of microalgal were in the pH range of 7–9. These findings show that it is feasible to cultivate microalgae in POME with a suitable amount of organic and inorganic compound.